Autoantibodies directed against the protease inhibitor calpastatin in psoriasis - Matsushita, Y (Blackwell Science Inc, 2005)
Psoriasis is believed to be a T cell-mediated autoimmune disease, but also exhibits autoantibody production. Calpastatin is an endogenous inhibitor of calpain, a ubiquitous protease that regulates inflammatory processes. Anti-calpastatin autoantibody was first identified as an autoantibody specific to rheumatoid arthritis, but has been also detected in other autoimmune diseases. In this study, we examined the presence and levels of anti-calpastatin antibody in 77 psoriasis patients by enzyme-linked immunosorbent assay. Compared with normal controls, psoriasis patients exhibited significantly elevated IgG anti-calpastatin antibody levels that were similar to those found in rheumatoid arthritis patients. Remarkably, IgG anti-calpastatin autoantibody in sera from psoriasis patients inhibited calpastatin activity. Calpain II expression was up-regulated in psoriasis skin lesions compared with normal skin while calpastatin expression was normal. The results of this study reveal the presence of anti-calpastatin autoantibody in psoriasis.